Developing a National Newborn Genomes Program: An Approach Driven by Ethics, Engagement and Co-design - Pichini, Amanda; Ahmed, Arzoo; Patch, Christine; Bick, David; Leblond, Mathilde; Kasperaviciute, Dalia; Deen, Dasha; Wilde, Simon; Garcia Noriega, Sofia; Matoko, Christella; Tuff-Lacey, Alice; Wigley, Chris; et al. (Frontiers in Genetics, 2022)
The transformative potential of whole genome sequencing (WGS) as a diagnostic tool in healthcare has been demonstrated by initiatives including the 100,000 Genomes Project and is now offered to certain patients in the National Health Service (NHS) in England. Building on these foundations, the utility of WGS in the newborn period can now be explored. Genomics England is working in partnership with NHS England and NHS Improvement and other healthcare, patient and public interest groups to design a research program embedded in the NHS to explore the potential challenges and implications of offering WGS in all newborns. The program will aim to: 1) evaluate the feasibility, utility and impact on the NHS of screening for childhood-onset rare actionable genetic conditions; 2) understand how, with consent, genomic and healthcare data could be used to enable research to develop new diagnostics and treatments; and 3) explore the implications of storing an individual’s genome for use over their lifetime. Recognizing the important practical, scientific and ethical questions that we must explore in dialogue with the public and experts, we are taking a collaborative, evidence-based and ethically deliberate approach to designing the program. An iterative co-design process including a nationwide public dialogue has identified emergent themes and ethical considerations which are the focus of the program’s design. These themes will be further developed through continued engagement with healthcare professionals, researchers, ethics experts, patient groups and the public, with an ongoing commitment to embedding ongoing ethics research and co-design into the delivery of the program.